NEXUS Gains Initiative to develop strategy for efficient dairy production in water-stressed region of Nepal - Varijakshapanicker, Padmakumar; Hatew, Bayissa; Jones, Christopher S.; Aryal, Anil; Nepal, Santosh; McCartney, Matthew P. (International Livestock Research Institute, 2023)
Animal husbandry and dairy production are key sources of nutrition and livelihoods in Nepal. Out of the 3.8 million farming households in the country, 95% have dairy animals providing food, income and other benefits.